Quantitative Leader-Member dynamics for church growth: Perez Chapel home cell - Charles Agyinasare (African Journal of Pentecostal Studies)
Background: Church growth remains a central theme in Pentecostal missiology, with small groups or home cells emerging as effective structures for qualitative and quantitative growth. Understanding the dynamics that foster this growth is critical, particularly within Pentecostal and Charismatic contexts.